Description of Logical Thinking Ability and Concept Hormones Systems in Class XI - Herman Sopian (Universitas Sebelas Maret, 2015)
This study aimed to obtain information about logical thinking ability and understanding of the concept of students on hormonal system. This study was conducted in class XI in one of the high schools in the Serang city. The method used descriptive quantitative. This quantitative descriptive method to describe, explain and interpret the logical thinking ability and understanding of students on the hormonal system concept by using instruments such as diagnostic tests, the three-tier test, and test of logical thinking (TOLT). The sampling of population was done by cluster random sampling as many as 33 students. Based on the results obtained that TOLT categorized either proportional reasoning, reasoning control variable and low category correlational reasoning, and reasoning probability and combinatorial reasoning sufficient category. Based on the three-tier test results showed that students had difficult understanding especially on subconcepts hormone function as well as differences in the hormone system and nervous system.Keywords: Concept understanding, Logical thinking, Three tier test, Test of logical thinking